QUESTIONS OF PREVENTION OF ALCOHOLISM AND RELATED CRIMES - Urazaliev Murod Koraevich (PT. Antis International Publisher, 2025)
Objective: Alcoholism remains a significant public health and social issue globally, closely tied to the emergence and escalation of criminal behavior. In Uzbekistan, legal and societal measures have been enacted to control alcohol consumption and reduce alcohol-induced offenses, particularly among vulnerable populations such as minors. Despite existing laws and preventive mechanisms, a gap persists in the practical implementation and legal precision needed to effectively prevent and sanction crimes committed under the influence of alcohol. This study aims to assess the relationship between alcoholism and criminal behavior, evaluate the effectiveness of current legal frameworks, and propose amendments to improve preventive and punitive responses. Method: The analysis reveals systemic shortcomings in the application of Article 261 of the Criminal Code of Uzbekistan and highlights areas needing reform, including stricter criminal liability for intoxicated offenses, targeted public health strategies, and institutional support for juvenile protection. Result: The article uniquely integrates legal, medical, and cultural dimensions in addressing alcohol-related crimes and recommends legislative amendments that align with international standards. Novelty: Implementing the proposed reforms—such as enhanced sentencing guidelines, broader definitions of criminal consequences under intoxication, and comprehensive youth protection mechanisms—can strengthen Uzbekistan's legal and preventive framework. These measures will not only help mitigate the social and economic burden of alcoholism but also contribute to the development of a healthier, more law-abiding society.